Variant Median Nerve Anatomy: Ultrasound Evidence of a Pseudoconduction Block. Issue 4 (June 2021) - Abrams, Rory M. C.; Pedowitz, Elizabeth J.; Simpson, David M.; Shin, Susan C.
Abstract: Introduction: A conduction block at a noncompressible site warrants further investigation. Methods and materials: A 36-year-old woman with a history of Hodgkin lymphoma and chemotherapy-induced polyneuropathy developed bilateral hand numbness and paresthesias. Workup revealed bilateral carpal tunnel syndrome and an apparent superimposed conduction block of the median nerve in the forearm. Given the history of cancer, there was concern for an infiltrative or an immune-mediated process. Results: Neuromuscular ultrasound demonstrated that the median nerve descended the upper extremity along an atypical path, deep along the posteromedial aspect of the upper arm, and relatively medially in the forearm. Ultrasound-directed nerve stimulation revealed there was no conduction block. This anatomical variant has been rarely described and has not been reported previously to mimic conduction block or been documented via ultrasound. Conclusions: This case demonstrates that neuromuscular ultrasound may supplement the electrodiagnostic study and limit confounding technical factors because of rare anatomic variation.